Variação espaço-temporal do espelho d'água na Lagoa Feia, RJ - Lima, Vinícius Santos (2014)
The study of lacustrine environments is conducted primarily in the field of biology, notably in Limnology. In the field of Geographic Science these water bodies historically not received its due attention. The lagoa Feia, part of the basin of the same name, is located between the cities of Campos dos Goytacazes and Quissamã, the northern state of Rio de Janeiro. Historically lagoa Feia suffered great loss in its water surface due to anthropogenic activities. In this sense, the work is mainly aimed to conduct a study of the spatio-temporal variation of the water surface of the lagoa Feia and surrounding identifying the main anthropogenic interventions. For the central goal was reached it became necessary to divide the work into separate steps that come from careful review general and specific literature, acquisition of cartographic materials and field campaigns to the application of GIS techniques for spatial analysis and RS. Perform spatial analysis allowed the physiography within the basin of the lagoa Feia and better understand natural and anthropogenic processes that markedly altered the net surface area of the lagoa Feia, namely the construction of dikes and canals (both governmental and private) and rectification of rivers are changes that led to loss of the water surface; flooding and consequent measure of environmental restoration: the implosion of the dikes (are changes that led to the gain in water surface).